O lúdico para o ensino da matemática: contribuições metodológicas - Silva, Jéssica Cristina da (2020)
This work was elaborated through researches and bibliographic, in order to study possible mathematical reasoning skills in elementary school children, through playful practices that contributed to the development of creativity, reasoning, socialization and interaction between theory and practice. A list of games and games that explored the integral development of the student in both cognitive and social aspects was analyzed. In view of the studies, it was realized that different teaching strategies and methodologies can contribute to the advancement and effectiveness of learning, in addition to promoting better pedagogical interventions by the teacher.